Design, synthesis and biological evaluation of edaravone derivatives bearing the N-benzyl pyridinium moiety as multifunctional anti-Alzheimer's agents - Luke S. Zondagh; Sarel F. Malan; Jacques Joubert (Taylor & Francis Group, 2020)
A series of multi-target directed edaravone derivatives bearing N-benzyl pyridinium moieties were designed and synthesised. Edaravone is a potent antioxidant with significant neuroprotective effects and N-benzyl pyridinium has previously exhibited positive results as part of a dual-site binding, peripheral anionic site (PAS) and catalytic anionic site (CAS), acetylcholinesterase (AChE) inhibitor. The designed edaravone-N-benzyl pyridinium hybrid compounds were docked within the AChE active site. The results indicated interactions with conserved amino acids (Trp279 in PAS and Trp84 in CAS), suggesting good dual-site inhibitory activity. Significant in vitro AChE inhibitory activities were observed for selected compounds (IC50: 1.2-4.6 µM) with limited butyrylcholinesterase inhibitory activity (IC50's >160 µM), indicating excellent selectivity towards AChE (SI: 46 - >278). The compounds also showed considerable antioxidant ability, similar to edaravone. In silico studies indicated that these compounds should cross the blood-brain barrier, making them promising lead molecules in the development of anti-Alzheimer's agents.